A REVIEW LITERATURE EMPLOYEE PERFORMANCE MODEL: MOTIVATION, LEADERSHIP STYLE AND ORGANIZATIONAL CULTURAL - Fahmi, Idham; lima Krisna, Nandan (Dinasti Publisher, 2021)
This article aims to study the effect of motivation, leadership style, organizational culture, and employee performance. The method of writing this scientific article is to use qualitative methods and library research. The results of this literature review article are: motivation, has a positive and significant effect on employee performance, leadership style has a positive and significant effect on employee performance, and organizational culture has a positive and significant effect on employee performance.